Rancang Bangun Driver PZT dan Filtering Data Akustik Pada Sonar Aktif - Adhi Kusuma Negara; Henry Manik; Susilohadi Susilohadi (Jurnal Rekayasa Elektrika, 2022)
Acoustic transducer is a source level component in the sonar equation that is indispensable as an underwater acoustic energy source, with a certain emission pattern called beamforming. In this research, we designed the construction of a driver circuit to trigger a piezoelectric (PZT) transducer to produce an acoustic energy beam for the purpose of detecting underwater targets. The manufacture of an acoustic driver with a simple working principle has been carried out to provide transmit (TX) and receive (RX) commands. The RX module will receive the acoustic signal from the TX and the results are recorded for analysis. The mixing of the information signal with noise makes the information obtained cannot be directly verified so that a signal processing process is needed to be able to separate the information signal and noise. Calibration using a spherical target was carried out to determine the detection results and the acoustic intensity level. Signal analysis and visualization methods use Fast Fourier Transform (FFT) and wavelets.